KONTRIBUSI LAHAN HUTAN KEMASYARAKATAN (HKm) TERHADAP PENDAPATAN KELOMPOK TANI HUTAN (KTH) - , ANDIKA ANGGIRIYAWAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In the management of the forest occur mutual related and required between forests and society. it appears in the activity forest management and also the utilization forest by local residents mutual benefit. The activities and the utilization of the forest management is very influential towards the welfare of the communities surrounding the forest, one of them is the increasing of people income. This research aims to know the contribution of forest utilization toward people's income in Desa Getas, Kecamatan Playen, Kabupaten Gunung Kidul. The collection of samples conducted by purposive sampling method. The method of collecting data by the questionnaire for communities of land holder Hutan Kemasyarakatan Gubugrubuh. The data is collected primary and secondary then analyzed in descriptive by approach of qualitative and quantitative. Based on the research result could be known that the activites and the utilization of the forest community are institutions and management. The results of analysis obtained show that the contributions from land utilization toward the area holders communities's income are 11,14 % or Rp 207.346,00. The average of per month from the income total each landholder is Rp 1.861.971,00.